2021
DOI: 10.1016/j.amjmed.2021.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in Heart Failure with Reduced Ejection Fraction: Progress, Not Problem

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A pharmacist is an important element of the multidisciplinary team, and several studies have demonstrated the effectiveness of such an approach to improve the overall quality of medication prescribing in older adults [298].…”
Section: Genetic Counsellingmentioning
confidence: 99%
“…A pharmacist is an important element of the multidisciplinary team, and several studies have demonstrated the effectiveness of such an approach to improve the overall quality of medication prescribing in older adults [298].…”
Section: Genetic Counsellingmentioning
confidence: 99%
“…Other adverse effects of polypharmacy include higher rates of malnutrition, increased urinary incontinence, which is more common in women over 70 years-of-age, increased risk of cognitive impairment (especially delirium) and a reduced ability to perform activities of daily living ( 44 ). These reports emphasize the importance of a multidisciplinary approach to the care of older adults to combat this risk, including a pharmacist and elder care specialist ( 48 ). Previous studies have demonstrated the effectiveness of a multidisciplinary approach to improve the overall quality of medication prescribing in older adults ( 44 ).…”
Section: Care Considerations Of Older Attr-cm Patientsmentioning
confidence: 99%
“…This perspective discourages the prescription of additional potentially beneficial treatments in such individuals. [8][9][10][11][12] Inappropriate prescribing may even lead to patients receiving harmful drugs. 13 However, in a recent analysis of the DELIVER trial ( Fraction Heart Failure), the relative reduction in the risk of the primary endpoint with sodium-glucose cotransporter 2 inhibitor treatment was at least as large in patients with polypharmacy as in those without; indeed, there was a trend to a greater reduction in patients taking a larger number of medications (p = 0.06 for interaction between number of drugs and effect of dapagliflozin).…”
Section: Introductionmentioning
confidence: 99%
“…These concerns often lead to the belief that new therapies will be less effective in older comorbid patients receiving multiple other drugs. This perspective discourages the prescription of additional potentially beneficial treatments in such individuals 8–12 . Inappropriate prescribing may even lead to patients receiving harmful drugs 13 .…”
Section: Introductionmentioning
confidence: 99%